Enhancing collaborative research and scaling through engaging CGIAR, Research Institutes, Universities and Extension - Abegaz, Solomon; Getachew, Tesfaye; Belay, Berhanu; Solomon, Dawit; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
A workshop on partnership in scaling-up livestock technologies has been conducted on December 17 and 18, 2021 in Hawassa, at Haile Hotels and resorts. The workshop was attended by 23 participants (21 in person and two online) representing higher learning institutions, federal and regional research, the Ministry of Agriculture, CGIAR and an NGO. In addition to the opening and closing remark by Dr Fikiru Regassa, the state Minister for livestock sector, Seven presentations (two online) were made on various aspects of collaborative research and development pertaining to partnership and scaling up of livestock technologies. Group discussions were also conducted on topics related to partnership model and Scaling framework. With respect to partnership model issues related to good partnership, essentials of partnership, and lessons in managing partnership were discussed while for scaling framework issues related with ensuring readiness of technology for scaling, the scaling framework required for scaling livestock technologies and other related issues were points of discussion. After deliberating on the issues of partnership and scaling up the groups have forwarded suggestions that are believed to ensure efficient and sustainable partnership and scaling of livestock technologies.